Comminution Characteristics of Lithium Bearing Mica Ores From Different Devices - Wikedzi, A.; Leißner, T.; Fraszczak, T.; Peuker, U. A.; Mütze, T. (Tanzania Journal of Engineering and Technology, 2020)
This paper highlights on the comminution and to the lesser extent liberation properties of two greisen-type lithium bearing-mica ores (L1, L2) subjected to different breakage devices; cone crusher (CC), roller crusher (RC), rotor beater mill (RBM) and a screen mill (SM). The particle size distributions (PSD) of the products from each device were evaluated to search for an appropriate PSD model using Gates-Gaudin-Schuhmann (GGS) and Rosin-Rammler (RR) functions. To determine an appropriate function, coefficients of determination (R2 ) were used as a criterion. Due to budget constraint, only products from rotor beater mill (RBM) were examined for mineral liberation by an automated scanning electron microscope (SEM) technique. It was found that RBM, RC and SM products were better described by the RR model than the GGS model with higher R2 values of 0.97 to 1.0. However, cone crusher products for L1 were better described by GSS model, while that for L2 were better described by RR model. In terms of the spread of size distribution as indicated by RR model parameters, RC products were more uniformly distributed compared to those from other devices, for both ores. Also the RBM products were more scattered than those from other devices. The results indicate that the composition of individual ores affected the comminution products PSDs as different PSD model parameters were obtained for samples comminuted by same devices. The modal mineralogy indicated that both ores are rich in quartz, topaz, zinnwaldite and muscovite. Furthermore, the result indicates that, for both ores, the zinnwaldite phase is more enriched in the fraction < 250 µm. Moreover, better liberation of zinnwaldite is observed for L1 compared to L2. This could be explained by differences of the two ores in three aspects; the nature of mineral association, reduction ratio of the fractions analysed and the spread of the size distribution. Keywords: Comminution, mineral liberation, Rosin-Rammler distribution, particle size distribution, Gates-Gaudin-Schuhmann distribution